1986
DOI: 10.1111/j.1944-9720.1986.tb01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Speaking Proficiency in the Undergraduate Curriculum: Data from French

Abstract: Studies (22, p. 42) recommended the establishment of "language proficiency achievement goals for the end of each year of study at all levels, with special attention to speaking proficiencf In this same year, the American Council on the Teaching of Foreign Languages (ACTFL) launched the oral proficiency interview in academia through the Testing Kit workshops. Now, seven years later, academic interest in oral proficiency testing has developed to the point where some institutions are beginning to associate expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
84
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 9 publications
10
84
3
Order By: Relevance
“…of classroom instruction are also consistent with those of Magnan (1986) and Tschirner (1996) for French and German, respectively. The second question posed in this study is whether or not immersion instruction offers students a richer basis for the acquisition of Russian than that offered by traditional classroom instruction.…”
Section: The Current Studysupporting
confidence: 84%
“…of classroom instruction are also consistent with those of Magnan (1986) and Tschirner (1996) for French and German, respectively. The second question posed in this study is whether or not immersion instruction offers students a richer basis for the acquisition of Russian than that offered by traditional classroom instruction.…”
Section: The Current Studysupporting
confidence: 84%
“…This belief may be due to the fact that lecturers' average level of English is very close to that of students' (upper-intermediate) and that this falls short of students' expectations of being exposed to a rich input. In fact, the recommended pre-requisite for university teaching assistants in many US universities is advanced plus or superior (Magnan 1986). Along the same lines, no student mentions that the students' insufficient English is a problem while lecturers stress that local students are not enough proficient.…”
Section: Discussionmentioning
confidence: 98%
“…For example, in a study of 40 students of French at the University of Wisconsin, Magnan (1986) found a median proficiency level of Intermediate Low for the end of the 1st year of study (range from Novice Mid to Intermediate Mid/High); a median of Intermediate Mid for the end of the 2nd year (range from Intermediate Low to Advanced); a median of Intermediate High/Advanced for the end of the 3rd year (range from Intermediate Mid/High to Advanced/Advanced High); and a median of Advanced for the end of the 4th year (range from Intermediate Mid to Advanced High). Of utmost interest in the study, Magnan finds that "Students at the same level of oral proficiency may be en-3 rolled in different levels of study, and students of the same level of study may be at different levels of oral proficiency" (p. 430).…”
Section: The Issue Of Time On Task and Oral Projicienq Lmekmentioning
confidence: 98%